2018
DOI: 10.1080/14634988.2018.1497398
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the degradation of aesthetics Beneficial Use Impairment in the Toronto and region Area of Concern

Abstract: Toronto and Region was designated a Great Lakes Area of Concern in 1987 due to significant degradation of environmental quality and impaired beneficial uses, including Degradation of Aesthetics. Historically overflows of combined sewers, direct discharge of poorly treated industrial wastewater, contaminated storm water, and litter contributed to excessive floating debris, odour and unnatural turbidity along parts of the waterfront and in some sections of Area of Concern watersheds. Despite the perception of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Morphological-based approaches, which were once the only method of determining richness, are rapidly being complemented with DNA-based methodologies such as metabarcoding, greatly increasing the taxonomic information obtained from benthic samples 21,21,[32][33][34] . In this study, we have demonstrated the benefits of Previously, morphological-based biomonitoring in Toronto Harbour had focused on overall richness as the determining factor of lake health 15,16,35 . While this can be informative as to the overall quantity of macroinvertebrate taxa present in the lake, it neglects details on the composition of taxa and proportions of bioindicator groups in relation to other taxa.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Morphological-based approaches, which were once the only method of determining richness, are rapidly being complemented with DNA-based methodologies such as metabarcoding, greatly increasing the taxonomic information obtained from benthic samples 21,21,[32][33][34] . In this study, we have demonstrated the benefits of Previously, morphological-based biomonitoring in Toronto Harbour had focused on overall richness as the determining factor of lake health 15,16,35 . While this can be informative as to the overall quantity of macroinvertebrate taxa present in the lake, it neglects details on the composition of taxa and proportions of bioindicator groups in relation to other taxa.…”
Section: Discussionmentioning
confidence: 77%
“…Previously, morphological-based biomonitoring in Toronto Harbour focused primarily on overall richness as the determining factor of lake health 15,16,35 with limited investigation into the composition of taxa. While this can be informative as to the overall quantity of macroinvertebrate taxa present in the lake, it misses details on the proportions of bioindicator groups in relation to other taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, morphological-based biomonitoring in Toronto Harbour had focused primarily on overall richness as the determining factor of lake health with limited investigation into the composition of taxa 15 , 16 , 35 . While this can be informative as to the overall quantity of macroinvertebrate taxa present in the lake, it misses details on the proportions of bioindicator groups in relation to other taxa.…”
Section: Discussionmentioning
confidence: 99%
“…In 1994, eight beneficial uses in Toronto Harbour were identified as impaired (beneficial use impairments; BUIs 12 , 13 . In 1987, Toronto Harbour was designated as an Area of Concern (AOC) 13 and since then, there has been an increase in biological monitoring in the harbour 9 , 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Edge et al, 2018). Eight of Toronto's 11 waterfront beaches are now Blue Flag beaches; Aesthetic condition of local watersheds and the Toronto waterfront are generally excellent or good, and AOC waters are free of substances that produce persistent objectionable deposits, unnatural colour or turbidity, or unnatural odours (Dahmer et al, 2018); Bottom sediments along the waterfront are getting cleaner and the health of benthic communities have improved (RAP, 2013(RAP, , 2014; Levels of contaminants in fish continue to decline and there are no restrictions on consumption of many resident fish (Bhavsar et al, 2018); Aquatic habitat improvements, including the creation and restoration of habitat for migration, spawning, nursery, feeding, shelter and overwintering support an increased diversity of fish species along the waterfront (Hoyle et al, 2018;Veilleux et al, 2018;Choy et al, 2018).…”
Section: Where We Are: Current Conditionsmentioning
confidence: 99%